Influencia de la oleorresina de Capsicum chinense en la vida útil de la carne de res empacada al vacío y almacenada en refrigeración - Salazar Sánchez, Eduardo Alexander (2022)
The aim of this study was to evaluate the effect of the application of Capsicum chinense oleoresin on bacterial growth in vacuum-packed and refrigerated beef. The oleoresin was extracted with ethanol and capsaicin and dihydrocapsaicin were quantified by HPLC with a diode array detector. Two groups (G1 and G2) consisting of meat cuts (50 g) were evaluated: G1, application of 2.5 ml of oleoresin on the entire surface of each cut, and G2, control group. The meat cuts were vacuum packed and stored in refrigeration. Three samples from each group were withdrawn on days 0, 1, 15, 30, 45, 60, 75 and 90 of storage for pH measurement and for the count of total mesophilic aerobes, total psychrotrophic aerobes, lactic acid bacteria and Brochothrix thermosphacta. The oleoresin yield was 12.53 ± 0.30%. The concentration of capsaicin and dihydrocapsaicin in the oleoresin was 1.39 and 0.54 mg/g, respectively. The pH in G1 remained at adequate levels for more days and bacterial counts were lower than in G2-control. Under the study conditions, the useful life for G1 was determined to be 70 days, while for G2 it was 56 days. It is concluded that Capsicum chinense oleoresin applied to vacuum-packed and refrigerated beef prolongs its shelf life.